2016
DOI: 10.1038/srep34708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Association Between Retinal Vein Occlusion and the Risk of Atrial Fibrillation Development: A 12-Year, Retrospective Nationwide Cohort Study

Abstract: We aimed to evaluate the risk of atrial fibrillation (AF) development following retinal vein occlusion (RVO). We performed a nationwide propensity score-matched cohort study by retrospectively reviewing a database from the Korean National Health Insurance Service, comprising approximately 1 million random subjects. RVO and AF were diagnosed based on the Korean Classification of Disease codes. The RVO group was composed of patients with an initial diagnosis of RVO made between 2003 and 2007 (n = 1,801), excludi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…To date, several nationwide representative sample studies have been published using data f rom the KNHIS-NSC. [14][15][16][17] In the present longitudinal study, we examined the association between SSNHL and CCVD in 770 sociodemographically matched individuals extracted from a nationwide 11-year longitudinal cohort database of 1 025 340 South Korean patients. Interestingly, we found that patients with SSNHL had a significant increased risk of CCVD incidence, with an HR of 2.18 after adjustment for sociodemographic factors and the presence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several nationwide representative sample studies have been published using data f rom the KNHIS-NSC. [14][15][16][17] In the present longitudinal study, we examined the association between SSNHL and CCVD in 770 sociodemographically matched individuals extracted from a nationwide 11-year longitudinal cohort database of 1 025 340 South Korean patients. Interestingly, we found that patients with SSNHL had a significant increased risk of CCVD incidence, with an HR of 2.18 after adjustment for sociodemographic factors and the presence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to results from the present study, findings from another study found an increased risk of AF in patients with RVO, which may be explained by difference between the study designs or ethnicity of the populations. [ 44 ] Because RVO share risk factors with ischemic stroke, RVO may be interpreted as a stroke surrogate marker. [ 16 ] As such, AF detection in RVO may still be relevant especially since AF commonly develops asymptomatically, and the silent development of incident AF in patients with prior retinal vascular occlusions would infer greater risk of stroke in the absence of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has inevitable limitations as an analysis tool using health insurance claim data [ 10 ]. First, the cohort consisted of 2.2% of the eligible Korean population in 2002 by stratified random sampling; therefore, it had high representativeness in 2002.…”
Section: Discussionmentioning
confidence: 99%